The Influence of Service Quality on Customer Satisfaction at Cafe Maze Bandung - Panduadha, M Hasby; Ishak, Riani Prihatini (Review: Journal of Multidisciplinary in Social Sciences, 2025)
This study aims to analyze the influence of service quality on customer satisfaction at Cafe Maze Bandung. The research employs a quantitative approach by distributing questionnaires to 100 customers. The independent variable (X), service quality, is measured using five SERVQUAL dimensions: tangibles, reliability, responsiveness, assurance, and empathy. The dependent variable (Y), customer satisfaction, is assessed through seven indicators: product quality, price, service, emotional factors, convenience, repurchase intention, and recommendation. The results of a simple linear regression analysis show that service quality has a positive and significant effect on customer satisfaction, with a coefficient of determination (R²) of 0.950, indicating that 95% of the variation in customer satisfaction is explained by service quality. The correlation coefficient is 0.975, reflecting a very strong relationship between the two variables. These findings highlight that improvements in service quality directly enhance customer satisfaction. Therefore, it is recommended that Cafe Maze Bandung management focus on improving responsiveness and reliability aspects, which still have room for development.